P2 The veterans specific activity questionnaire as a patient reported outcome measure in pulmonary vasculitis and interstitial lung disease. (12th November 2019) - Sethi, R; Gawecki, F; Mohamed, M; Coker, RK; Ward, K; Shovlin, CL
Abstract : Introduction and aims: Patients with respiratory disease often report activity limitation that is not always adequately or efficiently described by existing physiological parameters or patient reported outcome measure (PROM) tools such as the MRC Dyspnoea Scale. 1 The Veteran's Specific Activity Questionnaire (VSAQ), modified in 2017 for UK use, can be self-administered in a few minutes and has been validated in multiple studies. 2 The aims of the current study were to evaluate the VSAQ in patients with interstitial lung disease and pulmonary vasculitis. Methods: Adult patients attending interstitial lung disease and pulmonary vasculitis clinics in a single centre were recruited. The VSAQ was self-completed by patients who underwent standardised pulmonary function assessments before clinical assessment incorporating assignment of the Birmingham Vasculitis Activity Score (BVAS) and MRC Dyspnoea Scale. Metabolic equivalents (METs) were calculated from the VSAQ by METs=4.74+0.97(VSAQ)-0.06(Age). Relationships between METs and physiological variables were evaluated using STATA IC v15.0. Results: Ninety-four patients were recruited, 45 with interstitial lung disease and 49 with pulmonary vasculitis. 44 were males. Ages ranged from 30–87 years, body mass index from 17.3–48.7 kg/m 2, and resting heart rate from 52–119bpm. Spirometric values averaged 80% of predicted; TLCO 60% predicted. Resting oxygen saturation ranged from 78–100%. METs ranged from 1.73–14.29 kcal/kg/hour (median 5.39) in the 94 patients, and BVAS score from 0–30 (median 5) in 35 vasculitis patients. The VSAQ captured dynamic changes better than the MRC Dyspnoea Scale, e.g. in one patient presenting with worsening dyspnoea, returning to baseline two weeks later: VSAQ score increased from 4 to 12 (METs from 5.38 to 13.14 kcal/kg/hour) but MRC Dyspnoea Scale only changed from 2 to 1. In preliminary analyses a significant inverse correlation was found between METs and resting heart rate [Spearman r=-0.38, p<0.01] and BVAS [r=-0.45, p<0.01]. There were positive correlations between METs and the forced vital capacity [r=0.26, p=0.02] and TLCO [r=0.41, p<0.01]. Conclusions: The VSAQ may be useful to describe patient activity, and in serial measurements to monitor a patient's condition in patients with parenchymal disease and also patients with vasculitic/inflammatory disorders. Reference: Gawecki, et al . QJM 2019:112;335–342. Myers, et al . Am Heart 2001;142(6):1041–1046.